Pengaruh adsorben bentonit terhadap kualitas pemucatan minyak inti sawit - Bahri, Syamsul (Balai Riset dan Standardisasi Industri Palembang, 2014)
Research on the effect of bentonite as adsorbent in the bleaching process of palm kernel oil was conducted. The study was designed using complete randomized design with 2 factors; the first factor was the percentage of bentonite as weight of volume: 1%, 2% and 3%, and the second factor was the volume of palm kernel oil: 100 ml, 200 ml and 300 ml. Firstly, experiment started by producing kernel oil by pressing the raw material at 10 g/cm2 and continued with the process of immersion with adsorbent at a temperature of 105Â°C for 1 hour. Oil products was tested according to the procedures of Coconut Palm Oil qualities include color, odor, taste, moisture content, free fatty acid levels in based on SNI 01-2901-2006 test standards, while pelicans oil parameter was tested by alcohol-KOH saponification process. The results showed that the percentage of the bentonite significantly effect on oil quality for color only, while the other parameters were not affected by the presence of the bentonite as an adsorbent. The processing optimum condition was 2% bentonite soaked 200 ml oil volume, which resulted yellow color as close as required in accordance with SNI.Keywords: bentonite, bleaching, palm kernel oil, colorAbstrakTelah dilakukan penelitian pengaruh adsorben bentonit pada proses pemucatan minyak inti sawit. Penelitian didesain dengan menggunakan rancangan acak lengkap 2 faktorial dimana faktor pertama yaitu persentase bentonit w/v (1%, 2% dan 3%) dan faktor kedua yaitu volume minyak inti sawit (100 ml, 200 ml dan 300 ml). Percobaan dilakukan dengan pembuatan minyak inti sawit melalui pressing pada 10 g/cm2 dan dilanjutkan dengan proses perendaman minyak dengan adsorben pada suhu 105Â°C selama 1 jam. Produk minyak diuji kualitasnya meliputi parameter warna, bau, rasa, kadar air, kadar asam lemak sesuai dengan standar uji SNI 01-2901-2006, sedangkan parameter minyak pelikan diuji dengan saponifikasi alkohol-KOH. Hasil penelitian menunjukkan bahwa persentase bentonit berpengaruh signifikan terhadap kualitas minyak untuk warna saja, sedangkan parameter lain tidak dipengaruhi oleh adanya bentonit sebagai adsorbent. Kondisi optimum yaitu 2% bentonit pada volume minyak 200 ml, dimana hasil warnanya mendekati kuning sesuai dengan yang dipersyaratkan Standar Nasional Indonesia.Kata kunci: bentonit, minyak inti sawit, pemucatan, warna